2022
DOI: 10.1108/jgr-05-2022-0047
|View full text |Cite
|
Sign up to set email alerts
|

Female directors and corporate innovation in family firms in India. Do leverage ratios and mandatory CSR expenditure matter?

Abstract: Purpose Based on data collected using the purposive sampling technique extracted from a secondary data source, this paper aims to examine the relationship between female directors and firm innovation. The paper also examines the impact of leverage ratios and corporate social responsibility (CSR) expenditure on the association between female directors and firms’ innovation. Design/methodology/approach The feasible general least regression technique was applied to overcome potential endogeneity issues associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…To be specific, the number of employees and the market value of the firm are positively related to investments in intangibles, validating our expectations. This, in turn, confirms that large and profitable firms devote more resources towards intangible asset investments, supporting previous evidence (Oware & Appiah, 2022). As far as fixed assets are concerned, a perusal of Table 2 shows that tangibility is adversely associated with investments in intangibles.…”
Section: Regression Analysissupporting
confidence: 85%
“…To be specific, the number of employees and the market value of the firm are positively related to investments in intangibles, validating our expectations. This, in turn, confirms that large and profitable firms devote more resources towards intangible asset investments, supporting previous evidence (Oware & Appiah, 2022). As far as fixed assets are concerned, a perusal of Table 2 shows that tangibility is adversely associated with investments in intangibles.…”
Section: Regression Analysissupporting
confidence: 85%
“…Regarding the impact of female executives on CSR, some research findings suggest that companies with female executives perform better in areas such as charitable donations [24]. Other studies have found that female executives lack the professional knowledge to improve enterprise innovation because they are more cautious about taking strategic risks, which suppresses innovation activities and restricts the expenditure of CSR [25]. When gender inequality is low, female directors facilitate fulfilling CSR.…”
Section: Female Participation In Managementmentioning
confidence: 99%
“…Barker and Mueller (2002) showed that executives with better education have a stronger ability to absorb new ideas and are therefore more receptive to innovation. Chen et al (2018) found that female directors tend to invest more in innovation, Naveed et al (2022) discovered that board gender diversity contributes to green innovation, and Oware and Appiah (2023) found that female directors in India's family firms have a negative association with innovation.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Barker and Mueller (2002) showed that executives with better education have a stronger ability to absorb new ideas and are therefore more receptive to innovation. Chen et al (2018) found that female directors tend to invest more in innovation, Naveed et al (2022) discovered that board gender diversity contributes to green innovation, and Oware and Appiah (2023) found that female directors in India's family firms have a negative association with innovation. However, Hambrick (2007) posits that although executives' demographic characteristics can be used as proxies for their cognition, the "black-box problem" that the use of demographic indicators cannot truly help to understand the psychological factors driving executive behavior.…”
Section: Theoretical Backgroundmentioning
confidence: 99%